(untitled) (Fiep Bulletin - online, 2014)
Cardiorespiratory fitness is one of the most important components of health-related fitness. High cardiorespiratory fitness during childhood and adolescence has been associated with a healthier cardiovascular profile during these years (Mesa et al. 2006 a, b) and later in life (Ruiz et al. 2006a, b). One of the most widely used tests to assess cardio respiratory fitness among children and adolescents is the 20-m shuttle run test (Léger et Lambert, 1982). In the pilot study on the representative sample of schoolchildren of Belgrade (5692 boys and 5358 girls) we examined potential differences in the 20-m shuttle run test between boys and girls, among consecutive grades (from 3rd to 8th grade /9-14 years/). Two-way ANOV A (2x6) were performed (factors: gender and grade). When the significant main effects were found, Bonferroni post-hoc test was performed. The significant main effect of gender (F1,11150 = 872.8; p<.01), grade (F5, 11150 = 246.0; p<.01), and their interaction (F5, 11150 = 26.6; p>.01) was found when the 20-m shuttle run test between boys and girls and among consecutive grades were compared. Post hoc analysis revealed higher run times in boys than in girls within all grades. When differences in the 20-m shuttle run test were observed within boys (between all consecutive grades), while girls stopped achieving better results after grades six. These findings are in line with the number of previous studies were performance on the 20-m shuttle run test improved linearly until the age 12 years in girls, without the reached plateau in boys. Further research relating other physical fitness components to cardio respiratory fitness should be additionally performed to establish more complex picture about the overall Serbian elementary schoolchildren fitness. Acknowledgment: This paper is the result of the projects „Improving the quality and accessibility of education in modernization processes in Serbia” No 47008 (2011-2014) and „The effects of physical activity application to locomotor, metabolic, psychosocial and educational status with population of the Republic of Serbia“ No III 47015 (2011-2014) financially supported by the Ministry of Education and Science of the Republic of Serbia. The study was also supported in part by grant from the Serbian Research Council (No175037 and No175012).